Nature-based mindfulness-compassion programs using virtual reality for older adults: A narrative literature review - Sadowski, Isabel; Khoury, Bassam (Frontiers in Virtual Reality, 2022)
The global population is aging at an unprecedented rate, increasing the necessity for effective interventions targeting the mental health needs of older adults. Technology addressing the aging process of older adults (i.e., gerontechnology) is an avenue for the efficient delivery of programs that enhance adult well-being. Virtual reality (VR) is a type of gerontechnology with the potential to improve mental health and well-being (e.g., by increasing resilience, mindfulness, compassion, connection with nature, and decreasing stress, depression, anxiety); however, evidence in this area is currently lacking and more rigorous research on the acceptability, feasibility, and effectiveness of mental health programming via VR for older adults, such as nature, mindfulness, or compassion-based interventions, is necessary. The present literature review: (a) explores, synthesizes, and critically evaluates the literature on older adult mental health, well-being and gerontechnology, with a focus on virtual reality-based nature, mindfulness, and compassion-based interventions; (b) examines research to date on the relationship between virtual reality technology and nature, mindfulness, and self-compassion; (c) identifies gaps, contradictions, and limitations of existing research; (d) identifies areas for further investigation; and (e) discusses implications for research and clinical practice.